PELAKSANAAN PEMBERSIHAN KAMAR TAMU OLEH PRAMUGRAHA DI HOTEL NARIPAN BANDUNG - Simatupang, Devid; Mulyadi (Puslitabmas Batam Tourism Polytecnic, 2022)
The key to make guestroom looks tidy is by implementing room cleaning of standard operational procedure each hotel. Standard operating procedure is a standard where there is a special rule, principle, or action that is set as a reference for employees in carrying out their duties consistently. In a cleaning process at the hotel, it also need some proper and complete equipment as well as some cleaning materials that are suitable for their use. By interviewing housekeeping supervisors, the researcher obtained data regarding the number of cleaning equipment used by the room attendant in cleaning one room. The lack of equipment that is still lacking is metallic pressure. As for cleaning supplies, room attendant have their needed by request it. Researcher also asked for responses from room attendant regarding the completeness of work equipment, whether electronic or not, cleaning supplies used, and from the results obtained, room attendant said all equipment was in good condition. There are still guest complaints about the cleanliness of the guest rooms, especially on the condition of the floor, the cleanliness of the bed, the cleanliness of the pillow nests, and the cleanliness of the sheets. Likewise, the cleanliness of the bathroom which includes the cleanliness of the shower cabin, the cleanliness of the toilet bowl, and the cleanliness of the floor in the bathroom, this results in guest dissatisfaction with the services provided by the hotel.